Element Mobilization During Weathering Process of Ultramafic Complex in North Konawe Regency, Southeast Sulawesi Based on A Profile from Asera - Ronaldo Irzon; Baharuddin Abdullah (Geological Agency, 2018)
DOI: 10.17014/ijog.5.3.277-290The North Konawe Regency, located in the northern part of the southeast arm of Sulawesi Province, is occupied mainly by Ophiolite Complex. Recent studies on weathering of ultramafic complex have been focussed on the composition of laterite in relation to heavy metal explorations. In Asera area, North Konawe, a 3.1 m wide outcrop of ultramafic rocks is related to nickel laterite potential. In this study, an elemental change during the weathering process is discussed, including the mobilization of rare earth elements. XRF and ICP-MS from The Centre for Geological Survey of Indonesia are the two important geochemistry instruments used in this study. Si, Mg, and Ca are depleted during weathering, whilst the enriched elements are Fe, Al, Ti, and some heavy metals such as Cr, Mn, and Co. A different mobilization pattern is detected on Ni, because of its relation to Mg. Cs, Rb, and Ba are concentrated in a clayey horizon of upper laterite. The increase of REE concentrations is parallel to both Fe and Mn which rises to the top of laterite. Ce and Eu negative anomaly trends indicate oxidizing condition through the weathering process, although the studied profile, influenced by allochthon material, morphology condition, and geochemistry composition, indicates that the transported rock fragments were originated from ultramafic rock.